Mechanical Degradation of Different Classes of Composite Resins Aged in Water, Air, and Oil - Ricci, Weber Adad [UNESP]; Alfano, Priscila [UNESP]; Pamato, Saulo; Santos Cruz, Carlos Alberto dos [UNESP]; Pereira, Jefferson Ricardo (Hindawi Ltd, 2019)
A significant deterioration of the properties can drastically compromise the survival rate of restorative materials. The aim of this study was to assess flexural strength and hardness of three composite classes: hybrid composite resin (HCR), nanoparticulate composite resin (NCR), and silorane-based composite resin (SBCR). One hundred specimens were prepared for hardness testing by using a split metallic mold measuring 10 mm in diameter and 2 mm deep. Twenty specimens were prepared for each restorative material, randomly assigned for storage in air, distilled water, or mineral oil. After intervals of 24 hours, 30, 60, 90, and 120 days, hardness and flexural strength tests were initially compared in two levels: storage medium and time within each material group. A two-way analysis of variance was performed (p<0.05) on the variables material and storage time (p<0.05). The HCR showed to be stable with regard to the evaluation of flexural strength and hardness (p<0.05). A significant reduction occurs for the NCR in comparison to the other groups (p<0.05). The NCR presented the lowest values of hardness and flexural strength kept on water over time. The characteristics of material showed a strong influence on the decrease of the mechanical properties analyzed.